Psychological and physiological changes to the cold pressor test in adolescent handball players with normal menstruation - Sziráki, Z.; Alszászi, G.; Almási, G.; Annár, D.; Zsákai, A.; Nyakas, C.; Szmodis, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The menstrual cycle involves significant changes in hormone levels, which cause physical and psychological changes in women, which are further affected by stress. The cold-pressor test (CPT) in which subjects immerse their forearms in ice water is among the most commonly used laboratory stressors.